Discharge, microstructural and mechanical properties of ZrO2 addition on MgO for plasma display panel materials - Bakri, Jufriadi; Sutjipto, Agus Geter Edy; Othman, Raihan; Muhida, Riza (Maney Publishing, 2009)
One of the major parts in the plasma display panel is its protecting layer. MgO thin film has been widely used as a protective layer for dielectric materials. Adding another material to the MgO base material is an alternative method for improving its property as protective layer. A study on reducing the surface discharge potential of a single pure MgO protecting layer by the addition of ZrO2 with several compositions is presented in this paper. The microstructural and mechanical properties are also described. The discharge properties were measured utilising the flashover treeing for material characterisation, produced by a scanning electron microscope. The mechanical properties were measured using the pure bending moment. The MgO and ZrO2 powders with 99.95 and 99% purity were used for powder mixtures of various desired compositions. In this work, investigation was carried out for sintered samples at 1250 C for 24 h. From observation, ZrO2 addition into high purity MgO has influenced the properties of MgO. Since secondary electron emission coefficient contributes in increasing the electrical field of the surface, it could be found that 5 wt% ZrO2 added MgO has the highest secondary electron emission coefficient because the charging and discharging process happened within a shorter time.